Development of 100-MPa green reactive powder concrete using 100% recycled aggregates - Naidanjav, Undram; Ochirbud, Munkhtuvshin; Choi, Donguk (Journal of Asian Concrete Federation, 2022)
Reactive powder concrete (RPC) utilizing recycled resources such as silica fume, fly ash, waste glass powder, and recycled fine aggregates (RFA) was developed based on an experimental packing density methodology. Primary aim was to develop 100-MPa grade RPC using 100% RFA. Two different mix series were studied: First series (Series 1) was a control group and used conventional ingredients: ordinary Portland cement (OPC), silica fume, and silica sand. Second series (Series 2) also used OPC and, in addition, heavily utilized recycled resources such as silica fume, fly ash, waste glass powder, and RFA. Chemical admixtures (superplasticizer and defoaming agent) were used in all mixes. From Series 1, 100-MPa grade RPC was developed at water-binder ratio (w/b) = 0.22. From Series 2, the comparable strength grade RPC was developed at w/b = 0.18. It is shown that environmental-friendly RPCs can be systematically fabricated using 100% recycled sand and up to 30% substitutive cementitious materials.